2018
DOI: 10.1093/ofid/ofy014
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus-1 Drug Resistance Patterns Among Adult Patients Failing Second-Line Protease Inhibitor-Containing Regimens in Namibia, 2010–2015

Abstract: Three hundred sixty-six adult patients in Namibia with second-line virologic failures were evaluated for human immunodeficiency virus drug-resistant (HIVDR) mutations. Less than half (41.5%) harbored ≥1 HIVDR mutations to standardized second-line antiretroviral therapy (ART) regimen. Optimizing adherence, viral load monitoring, and genotyping are critical to prevent emergence of resistance, as well as unnecessary switching to costly third-line ART regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…However, as the access to ART continues to expand rapidly worldwide, often without adequate virological monitoring of patients on ART, emergence and transmission of HIV drug resistance (HIVDR) is a valid concern [ 2 ]. Studies in resource-limited settings have suggested that transmitted HIVDR in recently HIV-infected populations or pre-treatment HIVDR (PDR) in ART eligible patients is rising in countries where access to ART has been expanded [ 3 11 ], while acquired HIVDR (ADR) in patients on ART has been detected in majority of the patients failing ART [ 4 , 9 , 12 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as the access to ART continues to expand rapidly worldwide, often without adequate virological monitoring of patients on ART, emergence and transmission of HIV drug resistance (HIVDR) is a valid concern [ 2 ]. Studies in resource-limited settings have suggested that transmitted HIVDR in recently HIV-infected populations or pre-treatment HIVDR (PDR) in ART eligible patients is rising in countries where access to ART has been expanded [ 3 11 ], while acquired HIVDR (ADR) in patients on ART has been detected in majority of the patients failing ART [ 4 , 9 , 12 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of second-line ART failure in sub-Saharan Africa [ 10 ], the second-line failure rate among 18,550 people was 15 per 100 person years. In reports from clinical centers where HIV-1 genotyping had been performed in these patients, wildtype genotypes were observed in 12–58% of tested individuals [ 11 14 ]. Consistent with this, in genotyping at screening for the A5288 study of people from multiple LMICs failing second-line ART and hence being considered for possible third-line ART, approximately half (278, 51%) of 545 participants had no resistance to the PI they were taking and had no or minimal resistance to NRTIs and so continued their PI-based regimen.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence estimates of overall, drug class and drug-specific resistance observed in this study are broadly comparable to those observed in other countries [ 15 17 ] and in a recent retrospective non-representative convenience sample of 366 HIVDR genotypes obtained by Namibia's ART program during the period 2010 to 2015. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%